Gender Discrimination against Female Managers and Professionals in Sri Lankan Private Sector - Dharmawardhane, Iromi M.; Navaratne, N.N.J. (Asian Business Review, 2019)
Gender discrimination and sexual harassment contradict with the rights of women protected by law and practices at private sector organizations in Sri Lanka that may limit the career advancement of female employees. Several empirical researches on gender discrimination confirmed the impact of gender discriminations and sexual harassments on work motivation and productivity. However, this debilitating effect on the motivation and productivity of the female managers and professionals in Sri Lanka has not seen any empirical conclusion. The purpose of this study is to explore the relationship between workplace gender discrimination and sexual harassment with employees works motivation and productivity. The study conducted by selecting 66 female employees (44 female managers/ professionals, 22 HR managers) as a sample from 22 medium and large scale organizations covering the Sri Lankan private sector. Both quantitative and qualitative analyses conduct on collected data through a self-administered questionnaire. The results confirmed the incidents of gender discrimination and sexual harassment are present in recruitment and promotions activities in the selected organizations. However, the results did not support the relationships between gender discrimination and the loss of motivation and productivity at work.